Implementation of The Algorithm in a Web-Based Geographic Information System For Mapping Tourist Attractions in the Toba Area - Fadhil, Said Muhammad; Ikhwan, Ali (P3M Politeknik Negeri Bengkalis, 2024)
Tourism is an important economic sector, including in Indonesia, which has a wealth of natural and cultural destinations, such as the Toba region in North Sumatra. However, the lack of integration of most tourist attraction data in this area into the geographic information system (GIS) poses a challenge for tourists seeking complete and accurate information. This study creates a web-based GIS using the Average Nearest Neighbor (ANN) algorithm to look at how 31 tourist spots in North Tapanuli, Toba, and Humbang Hasundutan Regencies are spread out. We use the ANN algorithm to calculate the average distance between tourist attractions and their nearest points, yielding a T value of 0.516, which indicates a clustering pattern within the range of 0–0.7. Field surveys provided the data, which ArcGIS 10.8 processed and visualized in an interactive map on a web platform. We expect the implementation of this GIS to furnish the community and tourists with comprehensive and easily accessible information, and to aid the Tourism Office in managing and promoting tourist attractions. With the presence of GIS, tourism management in the Toba region can be more organized and efficient, increasing tourist visits through the presentation of interesting, complete, and accurate information in real time